Dermatoglyphics: A review on fingerprints and their changing trends of use - Anu Sharma; Veena Sood; Poonam Singh; Apoorva Sharma (Wolters Kluwer Medknow Publications, 2018)
Dermatoglyphics is a study of configurations of epidermal ridges on certain body parts, namely, palms, fingers, soles, and toes. The term is derived from ancient Greek: derma = skin, glyph = carving. Dermatoglyphic patterns begin to develop in the 10th week of gestation and are complete by the 24th week. Fingerprints of both hands are not the same and persist lifelong unless dermis is damaged. They are mainly under genetic control and can be used in the diagnosis of congenital malformations. Their uniqueness has led to the analyses of one's potential and preferences. During development, various creases develop on the brain and are reflected on fingerprints representing various regions of the brain and are commonly being used in dermatoglyphics mental intelligence test. Some parents have started analyzing their children' fingerprints in early age to understand their innate characters and learning potential in terms of personal, educational, or for preference in any other enterprise.